2017
DOI: 10.3390/ijms18091904
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Signaling Pathways in T-Cell Acute Lymphoblastic Leukemia

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive disease caused by the malignant transformation of immature progenitors primed towards T-cell development. Clinically, T-ALL patients present with diffuse infiltration of the bone marrow by immature T-cell blasts high blood cell counts, mediastinal involvement, and diffusion to the central nervous system. In the past decade, the genomic landscape of T-ALL has been the target of intense research. The identification of specific genomic alterations has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 260 publications
1
53
0
1
Order By: Relevance
“…It is well established that the PI3K/Akt/mTOR pathway is aberrantly activated in approximately 60% of T‐ALL patients (Silva et al, ) and correlates with a poor outcome (Bongiovanni et al, ). Our group previously showed that PI3K inhibition displayed strong cytotoxic effects on both ALL cell lines and primary cells, demonstrating that targeting PI3K could be an attractive strategy for treating ALLs (Bressanin et al, ; Evangelisti et al, ; Lonetti et al, ; Lonetti et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the PI3K/Akt/mTOR pathway is aberrantly activated in approximately 60% of T‐ALL patients (Silva et al, ) and correlates with a poor outcome (Bongiovanni et al, ). Our group previously showed that PI3K inhibition displayed strong cytotoxic effects on both ALL cell lines and primary cells, demonstrating that targeting PI3K could be an attractive strategy for treating ALLs (Bressanin et al, ; Evangelisti et al, ; Lonetti et al, ; Lonetti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatidylinositol 3‐kinase (PI3K)/Akt/mechanistic target of rapamycin (mTOR) and canonical Wnt/β‐catenin signaling pathways are implicated in healthy T‐cell development, whereas aberrations such as mutations, deletions, or overexpression of components belonging to the aforementioned networks contribute to T‐ALL pathogenesis (Bongiovanni, Saccomani, & Piovan, ; Evangelisti, Chiarini, McCubrey, & Martelli, ; Martelli et al, ; McCubrey et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although pediatric cases of T‐cell acute lymphoblastic leukemia (T‐ALL) have a cure rate exceeding 80% because of intensified chemotherapies and appropriate prognostic classifications, the outcome of T‐ALL patients with primary resistant or relapsed leukemia remains extremely poor . Recent insights into the biology of the disease have uncovered the genomic landscape of T‐ALL at diagnosis and defined T‐ALL subgroups . However, the molecular basis of refractory/relapsed T‐ALL is largely unknown, except for the involvement of NT5C2 mutations in relapsed T‐ALL .…”
Section: Introductionmentioning
confidence: 99%
“…Pathways related to the downregulated miRNAs were primarily related to TGF‐beta and NF‐κB signaling pathways and to apoptosis. NF‐κB signaling is a well‐known pathway involved in T‐ALL leukemogenesis due to pathway constitutive activation as well as through its antiapoptotic role . TGF‐beta signaling pathway is an important network involved on the control of hematopoiesis with a suppressing role in the growth of immune cells including T‐cells, and positive effects on T‐cell survival .…”
Section: Discussionmentioning
confidence: 99%